The Role of NGO's in the Realisation of the Right to Health in Uganda - Doreen Atuheirwe (Uganda Christian University, 2025)
This research study discusses NGO’s role in realising the right to health in Uganda, with a particular focus on NGO’s. It explores the legal and non-legal aspects governing role of NGO’s in realization of the right to health. It is a combination of library data collection analysis and doctrinal research it identifies the challenges that affect NGO’s in the realization of the right to health, the comparative models between South Africa and India in the way they handle the right to health and how Uganda as a country can adopt some of the methods and ways they use in making the right to health a fundamental human right for its population. This study recommends various amendments in the statutory laws of Uganda such as the Public Health Act, NGO Act and The Constitution of the Republic of Uganda 1995, as Amended, to acknowledge the right to health as a fundamental human right .